MOVIMENTO BROWNIANO: APLICAÇÃO EM ESTRATÉGIAS DE BUSCA - Matheus Dias Carvalho; Ricardo de Carvalho Falcão; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
This article has elucidated information about Brownian Motion in the ring, something that is still little explored in the literature. In addition, the ideas of feed, metabolic rate and stochastic restart to the walker were added, features that have been gaining ground recently in the study of random processes. This paper structured partial differential equations governing this process for the immortal case of walker, and later found analytical solutions to these expressions. The representation of stationary state was also performed in graphical form, thus obtaining the distribution function of probability required. In order to briefly approach the walker in a deadly process, a graph was produced that presents the function between the number of steps taken by a walker before his death and his metabolic capacity.